Characterising the plasma-target occupancy relationship of the neurokinin antagonist GSK1144814 with PET. (March 2014) - Ridler, Khanum; Gunn, Roger N; Searle, Graham E; Barletta, Julien; Passchier, Jan; Dixson, Luanna; Hallett, William A; Ashworth, Sharon; Gray, Frank A; Burgess, Clare; Poggesi, Italo; Bullman, Jonathan N; et al.
GSK1144814 is a potent, insurmountable antagonist at human NK1 and NK3 receptors. Understanding the relationship between plasma pharmacokinetics and receptor occupancy in the human brain, was crucial for dose selection in future clinical studies. GSK1144814 occupancy data were acquired in parallel with the first-time-in-human safety and tolerability study. [ 11 C]GR-205171 a selective NK1 receptor PET ligand was used to estimate NK1 occupancy at several time-points following single dose administration of GSK1144814. The time-plasma concentration–occupancy relationship post-single dose administration was assessed, and used to predict the plasma concentration–occupancy relationship following repeat dose administration. Repeat dose predictions were tested in a subsequent cohort of subjects examined following approximately 7 and 14 days dosing with GSK1144814. GSK1144814 was shown to demonstrate a dose-dependent occupancy of the NK1 receptor with an estimated in vivo EC50 ~0.9 ng/mL in the human brain. A direct relationship was seen between the GSK1144814 plasma concentration and its occupancy of the brain NK1 receptor, indicating that in future clinical trials the occupancy of brain receptors can be accurately inferred from the measured plasma concentration. Our data provided support for the further progression of this compound and have optimised the likely therapeutic dose range.